Developing an Assessment Instrument of Mathematical Problem-Solving Skills in Senior High School - Dyah Ayu Fitriana; Supahar Supahar (SAINTIS Publishing, 2019)
This study aims to develop an assessment instrument of mathematical problem-solving skills in senior high school. The developed assessment instrument includes instrument outlines, items of mathematical problem-solving skill in senior high school instrument, and scoring guidelines. The development procedures include 1) Planning the test, 2) Trying out the test, and 3) Establishing the Validity Test, 4) Establishing Test Reliability, and 5) Interpreting the Test Score. The trial was conducted on 508 respondents involving 4 experts and 1 practitioner as raters. The interpretation of the results of the trial is intended to find out the instrument construction and the validity and reliability of the assessment instrument. A problem-solving skill assessment instrument has been validated by the raters. Indicators to be measured include understanding problems, formulating strategies, implementing the strategies, and interpreting the results. The reliability coefficient of the results of the trial is categorized as good in which the Cronbach Alpha value is 0.82. Therefore, the developed instrument can be used to measure the mathematical problem-solving skills in senior high school.